A three-part coupled statistical and physical model to monitor water quality parameters governing disinfection byproduct risk at an urban drinking water intake - Hannoun, Deena; Tietjen, Todd (Frontiers in Water, 2022)
Extended drought in the twentieth century has led to loss of volume for lakes and reservoirs across the globe. In the Colorado River Basin, USA, Lakes Powell and Mead have experienced a 68% and 71% decline in volume, respectively, since 2000. Lake Mead is important to the Las Vegas Valley as it accounts for 90% of the source water used to serve the 2.2 million residents and 43 million annual tourists. Lake Powell is also vital to maintaining water quality in Lake Mead as it is located upstream and provides 97% of the water entering Mead. As Lakes Powell and Mead are projected to continue decreasing in volume over the next five years, it is important to understand the effects of loss of lake volume on water quality in this highly-managed system. Here, the effects of lake drawdown on water quality parameters that affect disinfection byproduct (DBP) formation in the source water for the Las Vegas Valley are projected over the next five years using Federal flow projections, regression modeling to project influent temperature from Lake Powell into Lake Mead, and a three-dimensional hydrodynamic and water quality model for Lake Mead. Results from these modeling efforts include projections for changes in values of water temperature, bromide, and total organic carbon (TOC) at the modeled cell that contains the Las Vegas Valley’s urban drinking water intake. Raw water bromide was found to have little change across modeled scenarios; however, raw water temperature is projected to increase because of falling lake surface elevations. Raw water TOC is projected to increase threefold in the simulated scenario that includes the most loss of volume but remains close to historic values in the remaining simulated scenarios. With these raw water quality projections, water managers can better plan for alterations to the water treatment processes, including mitigation of DBP formation.